Pengaruh Pemberian Kombinasi Kromium (III) Klorida dengan Vitamin C terhadap Kadar Kolesterol Darah Mencit Putih - Nori Wirahmi; Novi Elliyana; Surya Dharma (Jurnal Farmasi Higea, 2009)
Research about giving influence of combination of chloride (III) chromium with vitamin C to rate kolesterol white mouse blood has been done. Attempt animal is divided by five groups of that is group of control, group given vitamin C 0.52 mg/20 g body weight (BW), group given vitamin C 0.52 mg/20g BW and chromium (III) chloride with dose 5.2; 6.5; and 7.8 g /20g BW. Measurement of cholesterol rate done at day to day 8, 15, and 22 with enzimatis method applies spectrophotometer. Result of research show that giving of combination of chromium (III) chloride at dose 5.2; 6.5; and 7.8 g/20g BW give vitamin C 0.52 mg/20 g BW and give time depth can give influence to rate kolesterol white mouse blood.